Perceptions of the COVID-19 pandemic: a qualitative study with South African adults - Takana M Silubonde; Lucia Knight; Shane A Norris; Alastair van Heerden; Susan Goldstein; Catherine E Draper (BMC Public Health, 2023)
Abstract Introduction In South Africa, public perceptions of the COVID-19 pandemic and risk mitigation measures remain mixed. To better understand health behaviours in the context of COVID-19, a qualitative study was conducted, which aimed to investigate perceptions relating to the COVID-19 pandemic among the South African adult population. Methods Twelve online focus groups were conducted across the following age groups: 18–34, 35–54, 55 + years old (total n = 70) in December 2021. Diversity across socioeconomic status, geographical areas, and urban and rural settings was maximised, with an equal representation of men and women. Focus groups were conducted, and audio recorded using an online platform, transcribed verbatim and thematically analysed using MAXQDA. Results There were mixed perceptions around the pandemic, however, the majority of participants appreciated government actions at the onset of the pandemic and as a result government trust was reported to have initially been high. Nevertheless, as the pandemic progressed, challenges relating to government communication around the pandemic, the inconsistent application of preventative measures by government, the use of soldiers to enforce preventative measures, the banning of alcohol and cigarettes, government corruption and the pervasiveness of social media were reported to have eroded government trust, negatively impacting the uptake of preventative measures. Economic and psychological impacts were experienced differently across income groups. Low-income earners, who already had pre-existing economic challenges reported increased psychological and financial strain. While the once cushioned middle class reported an increase in job insecurity accompanied by psychological challenges. High income earners did not report economic challenges but reported being affected psychologically. Though, low-income earners reported an appreciation of the government financial relief afforded to them middle income earners appeared to not have received adequate financial support. Conclusion With the existing mistrust of government, there is need for government to leverage existing trusted sources in communities to aid in the implementation of preventative measures. These findings support the development of context specific solutions to address challenges faced at different socioeconomic levels.